FORMULASI NUGGET IKAN TUNA (Thunnus sp.) DAN LABU KUNING (Cucurbita moschata) SEBAGAI MAKANAN TINGGI PROTEIN DAN VITAMIN A UNTUK ANAK USIA SEKOLAH DASAR - Shafara, Frizka Arlyfia Firda; Hardiansyah, Angga; Widiastuti, Widiastuti (Jurnal Ilmu Gizi Indonesia (JIGZI), 2023)
Tuna and pumpkin are food ingredients that contain protein and vitamin A, so they can be processed into an alternative to fast food snacks that are nutrient-dense in the form of nuggets. It is necessary to increase the intake of protein and vitamin A nutrients, especially for elementary school-aged children where at that age problems of difficulty eating begin to appear while they need sufficient nutrients for growth and development, physical activity, and support learning achievement. The purpose of this study was to determine the effect of tuna and pumpkin substitution on panelists' acceptability and nutritional content. The experimental research design used a completely randomized design (CRD) with 6 treatments and 2 repetitions. The panelists in this study were 30 elementary school age children (10-12 years). Organoleptic analysis data were analyzed using the Kruskal Wallis test, if significant, continued with the Mann Whitney further test. Meanwhile, the results of the proximate test and vitamin A analysis were analyzed using the Independent Sample t-test. The results of organoleptic research showed that the nugget formula selected was F1 (15% tuna: 85% pumpkin). The results of the nutrient analysis of the selected formula based on SNI 7758-2013 showed the results of testing the water content of 56.69%, ash content of 1.86%, fat content of 2.58%, protein content of 5.17%, vitamin A content of 2742 RE of nugget products. meet the specified requirements, while for the carbohydrate content of 33.71% it has not met the SNI. The conclusion of this study was that the control formula nuggets were significantly different from the selected formula (p0.005) in the protein and vitamin A test.  Ikan tuna dan labu kuning merupakan bahan makanan yang mengandung protein dan vitamin A, sehingga dapat diolah menjadi alternatif snack cepat saji yang padat gizi berupa nugget. Peningkatan asupan zat gizi protein dan vitamin A perlu dilakukan, khususnya untuk anak usia sekolah dasar dimana pada usia tersebut permasalahan sulit makan mulai muncul sementara mereka membutuhkan zat gizi yang cukup untuk pertumbuhan dan perkembangan, aktivitas fisik, serta mendukung prestasi belajar. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh subtitusi ikan tuna dan labu kuning terhadap daya terima panelis dan kandungan gizinya Desain penelitian eksperimental ini menggunakan Rancangan Acak Lengkap (RAL) dengan 6 perlakuan dan 2 kali pengulangan. Panelis dalam penelitian ini sebanyak 30 anak usia sekolah dasar (10-12 tahun). Data analisis organoleptik dianalisis menggunakan uji Kruskal Wallis, apabila signifikan dilanjutkan dengan uji lanjut Mann Whitney. Sedangkan hasil kadar uji proksimat dan analisis vitamin  A dianalisis menggunakan uji Independet Sample t-test. Hasil penelitian organoleptik menunjukkan nugget formula terpilih  adalah F1 (15% ikan tuna: 85% labu kuning). Hasil analisis zat gizi formula terpilih berdasarkan SNI 7758-2013 menunjukkan hasil pengujian kadar air 56,69%, kadar abu 1,86%, kadar lemak 2,58%, kadar protein 5,17%,  kadar vitamin A 2742 RE produk nugget telah memenuhi syarat yang ditentukan, sementara untuk kadar karbohidrat 33,71% belum memenuhi SNI. Kesimpulan penelitian ini adalah nugget formula kontrol berbeda nyata dengan formula terpilih (p0,005) pada uji protein dan vitamin A.